2018
DOI: 10.4187/respcare.05717
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Pulmonologist Survey Regarding Knowledge and Practices With Inhalation Devices for COPD

Abstract: Most respondents were confident in their knowledge about treating COPD. Fewer respondents were confident about the use and maintenance of inhalation devices, and most respondents desired to learn more about inhalation devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Therefore, COPD patients may benefit from nebulized long acting bronchodilator therapy over a shorter treatment time period, to address compliance issues associated with longer administration times and dosing frequency. A recent survey evaluating pulmonologists' experiences with the use of small volume, handheld nebulizers in COPD disease management found that the majority of respondents considered nebulizers may be more effective than dry-powder inhalers or metered-dose inhalers for the treatment of severe COPD and acute exacerbations [32].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, COPD patients may benefit from nebulized long acting bronchodilator therapy over a shorter treatment time period, to address compliance issues associated with longer administration times and dosing frequency. A recent survey evaluating pulmonologists' experiences with the use of small volume, handheld nebulizers in COPD disease management found that the majority of respondents considered nebulizers may be more effective than dry-powder inhalers or metered-dose inhalers for the treatment of severe COPD and acute exacerbations [32].…”
Section: Discussionmentioning
confidence: 99%
“…There can be concern about not providing patient-specific inhalers in the hospital for patient education reasons, but unless most inhalers with varying device techniques are carried on formulary and the institution has routine comprehensive education for all the staff responsible for administering and teaching throughout the hospital stay then this model will still have inherent deficiencies and does not necessarily mean the drug is administered or taught correctly 10,11,38,39 . A recent study suggests that a high percentage of pulmonologists may not even have the skill set to teach all the medications they are potentially prescribing 40 . The other issue that confounds this is the fact that suboptimal PIFRs have been linked to COPD all-cause readmissions 13 .…”
Section: Discussionmentioning
confidence: 99%
“…25 However, a companion survey to the one presented here demonstrated that the majority of U.S. pulmonologists surveyed do not routinely consider SVNs as an option for maintenance therapy in patients with COPD. 15 Furthermore, only about half of surveyed U.S. pulmonologists reported discussing device options with their patients or screened for physical impairments that would impact delivery device choice, and only 16% screened for cognitive impairment. For optimal inhaled COPD therapy, the choice of the inhalation device needs to be matched to the patient's needs and preferences.…”
Section: Discussionmentioning
confidence: 99%
“…While 70% reported discussing how to use aerosol delivery devices during patients' first visit, only 9% discussed how to clean and store them. 15 These observations suggest more education, and reinforcement of that education, are warranted to ensure the best possible care for subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation